Analisis Determinan Orang Dengan Gangguan Jiwa (ODGJ) Rawat Inap Ulang di RSJD Provinsi Lampung - David , David; Setiaji , Bambang; Djamil , Achmad; Karyus , Aila; Dewi Rahayu (Jurnal Kesehatan Komunitas, 2024)
The burden of disease in Indonesia from mental disorders is 13.4%. People with re-hospitalized mental disorders become a burden on the family, and the determinants of this behavior include age, gender, education, and work and family knowledge. The study aimed to analyze the determinants of rehospitalization at the Regional Psychiatric Hospital Lampung Province. Methods; This type of quantitative research with cross-sectional design. The family population of ODGJ. The research sample comprised 404 people who completed interviews with 5 informants. Data analysis used univariate, bivariate (chi-square) multivariate analysis (multiple logistic regression). Result; there was no relationship between age (p= 0.459), gender (p= 0.251), and occupation (p=0.191) with rehospitalization. Meanwhile, the education variable (p=0.018; OR=2.060) and family knowledge (p=0.000; OR=3.107) showed a significant relationship with rehospitalization. The results of multivariate analysis showed that the most dominant determinant of rehospitalization was family knowledge (p=0.000; OR=3.04) after controlling for education variables. Conclusions and Suggestions: Age, gender, and occupation are not determinants of rehospitalization while education and knowledge of the family are determinants of rehospitalization in the Lampung Provincial Hospital. This study suggests education about the benefits of re-hospitalization: Provide clear and comprehensive information to patients and their families about the benefits of re-hospitalization.